Media Development Using Video with the ADDIE Model in the 4th Grade English Subject at the Karitas III Surabaya SDK - Achmad Noor Fatirul; Djoko Adi Walujo; Novianita Firda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to develop learning media in English lesson using video based on the ADDIE model at SDK Karitas III Surabaya. This development research is based on the lack of learning media to increase pronunciation in English lesson. To collect data about these problems, a questionnaire was used. Questionnaire used to provide a product assessment or product feasibility developed involving design experts, materials experts, and media experts. Meanwhile, to find out the responses of students, it was carried out by testing small groups, medium or limited groups, and large groups using the same questionnaire instrument. The results obtained in the product feasibility test showed that for design experts a percentage of 93% was obtained, for material experts the percentage was 80%, and for media experts the percentage was 93.3%. From the results of the expert feasibility test, it can be concluded that the product developed is said to be feasible for testing in the learning process. For small group trials, the percentage is 74.1%, for medium or limited group trials, the percentage is 82.1%, and for large group trials, the percentage is 88.5%. Based on the results conclude that the development product  for learning media in English subject especially Food and Drink material using video with ADDIE model at SDK Karitas III Surabaya is said to be feasible to be used and applied in the learning process as a guide to use in learning media.